Clinical Features and Outcomes of Strabismus Treatment in Third Cranial Nerve Palsy during a 10-Year Period - Bagheri, Abbas (J Ophthalmic Vis Res, 2014)
PURPOSE: To evaluate the demographics and management outcomes of strabismus surgery in patients with third cranial nerve palsy. METHODS: This retrospective study includes subjects with third cranial nerve palsy. We evaluated age, sex, laterality, severity of involvement, etiology, frequency of clinical findings, and types and results of treatments. RESULTS: 52 patients including 29 male and 23 female subjects with mean age of 21.1±15.5 years were studied between January 1999 and January 2009. Etiologies of third nerve palsy included congenital in 16 (30.8%), trauma in 26 (50%) and other causes in 10 (19.2%) patients. In 24 patients (46.2%), the palsy was complete. The most common type of strabismus was exotropia associated with hypotropia (40%). Medical treatment was used in 25 (48%) and surgical treatment in 46 (88.4%) subjects. One time strabismus surgery was performed in 30 (65.2%), 2 times in 11 (24%) and 3 times in 5 (10.8%) subjects. The most common operation was large horizontal recession and resection in 78.2% of cases. Mean horizontal deviation in primary position was 66±29 prism diopters (PD) before surgery decreasing to 21±19, 13±12 and 6±8 PD after first, second and third surgery, respectively. Corresponding figures for mean vertical deviation were 13±15, 7±12, 4±6 and 1±2 PD, respectively. Abnormal head posture was 10-30° in 11 (21.1%) cases before treatment which completely resolved after surgery. CONCLUSION: Surgical management of strabismus in patients with third nerve palsy is difficult and challenging, however the majority of patients achieve ideal results with appropriate and stepwise surgical plans.